Crimes arising from the use of genetic engineering methods (comparative study) - Nada Saleh Hadi ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2020)
Genetic engineering offenses are crimes that have not received the attention of the criminal legislator. Genetic engineering offenses vary in the variety ofmeans used; there are crimes arising from the misuse ofthe human genome and others arising from the disclosure or destruction of the information obtained from genetic testing Theft, sale or purchase, or the threat to use them for purposes other than the intended purpose. These crimes are subject to the general rules to which the other conventional crimes are governed by the Iraqi legislator in the Iraqi Penal Code, as well as the Egyptian legislator in the Penal Code, Because of the lack of special laws governing the provisions of these crimes, and we divided this study into two topics, we talked in the first of them about: What are the crimes of genetic engineering, through the statement of concept and legal basis, and then talked in the second section on: the provisions of genetic engineering crimes, Statement of the controls of the work by means of genetic engineering, and the elements of the crimes arising from them, and the conclusion of the most important findings of the researcher's findings and recommendations.